PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LIKUIDITAS, DAN FAKTOR LAINNYA TERHADAP FINANCIAL DISTRESS - FANUEL WILSON GUNAWAN; RINJANI (E-Jurnal Manajemen Trisakti School of Management (TSM), 2026)
This study aims to examine the effect of profitability, firm size, liquidity, and other factors on financial distress in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. The independent variables used in this study include profitability, leverage, liquidity, operating capacity, firm size, net profit margin, and earnings growth. The research was conducted using data from 80 manufacturing companies, resulting in a total of 240 observations. The data were analyzed using multiple linear regression with SPSS version 25. The results of the study show that liquidity have a positive and significant effect on financial distress. On the other hand, leverage and firm size have a negative and significant effect on financial distress. Meanwhile, profitability, operating capacity, net profit margin, and earnings growth do not have a significant effect on financial distress.